Cannabis use and the sperm epigenome: a budding concern?. Issue 1 (19th March 2020) - Schrott, Rose; Murphy, Susan K
Abstract: The United States is swiftly moving toward increased legalization of medical and recreational cannabis. Currently considered the most commonly used illicit psychoactive drug, recreational cannabis is legal in 11 states and Washington, DC, and male use is an important and understudied concern. Questions remain, however, about the potential long-term consequences of this exposure and how cannabis might impact the epigenetic integrity of sperm in such a way that could influence the health and development of offspring. This review summarizes cannabis use and potency in the USA, provides a brief overview of DNA methylation as an epigenetic mechanism that is vulnerable in sperm to environmental exposures including cannabis, and summarizes studies that have examined the effects of parental exposure to cannabis or delta-9 tetrahydrocannabinol (THC, the main psychoactive component of cannabis) on the epigenetic profile of the gametes and behavior of offspring. These studies have demonstrated significant changes to the sperm DNA methylome following cannabis use in humans, and THC exposure in rats. Furthermore, the use of rodent models has shown methylation and behavioral changes in rats born to fathers exposed to THC or synthetic cannabinoids, or to parents who were both exposed to THC. These data substantiate an urgent need for additional studies assessing the effects of cannabis exposure on childhood health and development. This is especially true given the current growing state of cannabis use in the USA.